Genetic tests for ability?: talent identification and the value of an open future - Miah, A.; Rich, E. (Sport, Education and Society, 2006)
This paper explores the prospect of genetic tests for performance in physical activity and sports practices. It investigates the terminology associated with genetics, testing, selection and ability as a means towards a socio-ethical analysis of its value within sport, education and society. Our argument suggests that genetic tests need not even be used (or widely used) as a tool for talent identification to have an impact on the way in which abilities are recognised and celebrated within sport. Just the development of these tests may consolidate discourses associated with performance and techno-scientific views of the bodies which are drawn upon in selecting, labelling and positioning some, rather than others, as `able`. The attachment of sports institutions to these technologies may be helping to shape a theoretical and wider social construction of how performance is viewed. Our paper problematises the place that such testing may assume in the culture of physical activity and potentially physical education. In doing so, we explore how the development of these tests may impact educational practices related to sport in two keys ways. Firstly, the direct impact in terms of the ways in which the information from these tests may be used to influence the sports experience of young people, within both physical education and sports arenas. Secondly, we consider how, on a broader level, the increasing importance given to genetic science may be (re)constructing wider social understandings of the nature of `ability` within sport and physical activity. Our response to these developments extends Feinberg's thesis on an `open future`, which argues that selecting the characteristics of children would be unacceptable on account of it diminishing the openness of that child's future—the range of prospects they might encounter that could lead to the flourishing of their life. On this view, we argue that genetic tests for performance might violate the child's right to an open future and that this concern should be taken into account when considering how and whether such tests should be used.